Pengaruh Afirmasi Positif terhadap Tingkat Kecemasan Anak saat Hospitalisasi di RSUD Dr. M.M Dunda Limboto - Parawouw, Dewi Carlina; Paramata, Nanang Roswita; Antu, Mihrawaty (Medical and Health Journal, 2025)
Anxiety is a response to unpleasant situations and is commonly experienced daily, particularly by children. One approach to addressing anxiety is through the use of positive affirmations. This study aims to analyze the effect of positive affirmations on children's anxiety levels during hospitalization at RSUD Dr. M.M. Dunda Limboto. This quantitative study utilized a quasi-experimental design with a non-equivalent control group approach. The sampling technique employed was incidental sampling, with a population of 177 respondents and a sample size of 38 respondents, including 19 in the intervention group and 19 in the control group. The instruments used in this research were a Standard Operating Procedure (SOP) for positive affirmations and the Visual Analog Scale for Anxiety (VAS-A) observation sheet. Non-parametric Wilcoxon testing was used for data analysis within the same group. The p-value for the intervention group was 0.000, indicating a significant change in anxiety levels before and after receiving positive affirmation intervention. In contrast, the p-value for the control group was 0.157, indicating no significant change in anxiety levels before and after the intervention. For data analysis between the two unpaired groups, an independent t-test was conducted, yielding a p-value of 0.001, indicating a significant difference in anxiety levels between the intervention group (receiving affirmations) and the control group (without affirmations) during hospitalization at RSUD Dr. M.M. Dunda Limboto. The study concludes that positive affirmations significantly affect children's anxiety levels during hospitalization at RSUD Dr. M.M. Dunda Limboto. Therefore, this study may serve as valuable information and input for RSUD Dr. M.M. Dunda Limboto to enhance the quality of hospital services and incorporate positive affirmations as an effort to reduce the impact of hospitalization on pediatric patients.